Rational design of highly active “hybrid” phosphine-phosphinite pincer iridium catalysts for alkane metathesis - Nawara-Hultzsch, Agnieszka J.; Hackenberg, Jason D.; Punji, Benudhar; Supplee, Carolyn; Emge, Thomas J.; Bailey, Brad C.; Schrock, Richard R.; Brookhart, Maurice; Goldman, Alan S. (ACS Catalysis, 2013)
Both the bisphosphine and bisphosphinite pincer complexes (tBu4PCP)IrH2 and (tBu4POCOP)IrH2 can cocatalyze alkane metathesis in tandem with olefin metathesis catalysts, but the two complexes have different resting states during catalysis, suggesting that different steps are turnover-limiting in each case. This led to the hypothesis that a complex with intermediate properties would be catalytically more active than either of these two species. Accordingly, “hybrid” phosphine–phosphinite pincer ligands (PCOP) and the corresponding iridium complexes were synthesized (3c–e). In tandem with olefin-metathesis catalyst MoF12, (tBu4PCOP)IrH2 displays significantly higher activity for the metathesis of n-hexane than does (tBu4PCP)IrH2 or (tBu4POCOP)IrH2. (tBu2PCOPiPr2)IrH4 (3d) is even more active (>30-fold more active than (tBu4POCOP)IrH2) and affords nearly 4.6 M alkane products after 8 h at 125 °C.